Resuscitation Fluids - Casey, Jonathan D. (Curr Opin Crit Care, 2018)
PURPOSE OF THE REVIEW: Intravenous fluid administration is a fundamental therapy in critical care, yet key questions remain unanswered regarding optimal fluid composition and dose. This review evaluates recent evidence regarding the effects of fluid resuscitation on pathophysiology, organ function, and clinical outcomes for critically ill patients. RECENT FINDINGS: Recent findings suggest that intravenous fluid composition affects risk of kidney injury and death for critically ill adults. Generally, the risk of kidney injury and death appears to be greater with semisyntheic colloids compared to crystalloids, and with saline compared to balanced crystalloids. Whether a liberal, restrictive, or hemodynamic responsiveness-guided approach to fluid dosing improves outcomes during sepsis or major surgery remains uncertain. SUMMARY: As evidence on fluid resuscitation evolves, a reasonable approach would be to use primarily balanced crystalloids, consider 2–3 liters for initial fluid resuscitation of hypovolemic or distributive shock, and use measures of anticipated hemodynamic response to guide further fluid administration.